2019
DOI: 10.5650/jos.ess18193
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Lipid Changes That Occur in Hypertrophic Muscle due to Fish Protein-feeding Using Mass Spectrometry Imaging

Abstract: Alaska pollack protein (APP) was previously shown to reduce serum triacylglycerol and the atherogenic index and significantly increase gastrocnemius muscle mass in rats. To determine which myofibers are involved in this observed hypertrophy, we stained the gastrocnemius muscle with fast and slow fiber-specific antibodies and measured the muscle fiber diameter. We observed muscle hypertrophy in both the fast and slow fibers of APP-fed rats. Although muscle hypertrophy leads to drastic lipid changes, the amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
1
9
1
1
Order By: Relevance
“…Relationships between the stimulation frequency and electrically elicited force are markedly influenced by contractile properties (39), and correlations between motor unit firing patterns and muscle contractile properties (7,8) have been reported in human skeletal muscles. In previous studies using rat muscle, significant increases in the gastrocnemius muscle weight and fiber diameters were observed by ingestions of APP, but not CAS, during 6-or 8-week interventions (10)(11)(12). In a human study, we also showed increases in the muscle volume of older adults with APP ingestion, but not of older adults with CAS ingestion, following 8 weeks of resistance training (9).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Relationships between the stimulation frequency and electrically elicited force are markedly influenced by contractile properties (39), and correlations between motor unit firing patterns and muscle contractile properties (7,8) have been reported in human skeletal muscles. In previous studies using rat muscle, significant increases in the gastrocnemius muscle weight and fiber diameters were observed by ingestions of APP, but not CAS, during 6-or 8-week interventions (10)(11)(12). In a human study, we also showed increases in the muscle volume of older adults with APP ingestion, but not of older adults with CAS ingestion, following 8 weeks of resistance training (9).…”
Section: Discussionsupporting
confidence: 67%
“…However, another study reported no significant changes in contractile properties in any types of muscle fibers following 12 weeks of resistance training in humans (44). In the present study, although physiological processes cannot be determined, the pathway leading to changes in the motor unit firing pattern following resistance training in the APP group could be alterations in muscle contractile properties caused by a modification of muscle protein synthesis processes due to APP intake (10)(11)(12). Further studies are needed to clarify the effect of APP ingestion on muscle contractile properties and its relationship with motor unit firing patterns.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Similarly, a recent study using 5-week-old male Sprague-Dawley rats showed that the volume of gastrocnemius increased in the APP-fed rats in comparison to the casein-fed animals. The results indicated a volume increase in both fast and slow fibers [50].…”
Section: Fish Proteins Function On Muscle Massmentioning
confidence: 86%
“…The fast and slow muscle fibers have different metabolic characteristics and are arranged in a heterogeneous manner in the skeletal muscle. Muscular atrophy and hypertrophy mainly affect fast fibers [50].…”
Section: Fish Proteins Function On Muscle Massmentioning
confidence: 99%